Pendampingan Pembuatan Nata De Fish Dari Limbah Rebusan Lemuru Sebagai Diversifikasi Produk Berbasis Zero Waste and Halthy Food di Desa Bomo Banyuwangi - Nadya Adharani (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Bomo Beach or commonly called Ria Bomo Beach is one of the beach destinations that has begun to be famous in Banyuwangi Regency since the last three years. One of the marine life commodities caught by fish that is still often found is lemuru fish. Lemuru that is caught is usually sold to the market or sold to local residents at a low price, but if it still does not sell well, the local community reprocesses it into several processed lemuru, one of which is commonly found is pindang lemuru. The decoction of lemuru from household industrial food (PIRT) in making lemuru pindang is usually thrown in the sewer that empties into the sea, thus impacting water pollution. Lemuru decoction actually still contains protein, fat, and omega 3, it can still be reused into processed fish products to increase the added value of a commodity, namely nata de fish. Program Kemitraan Masyarakat Programe (PKM) activities are carried out with the aim of increasing the level of fishermen's income by making nata de fish products based on product diversification